Boundary value problem for the four-dimensional Gellerstedt equation - Berdyshev, A.S.; Ryskan, A.R. (KU Publ., 2021)
In this work, the solvability of the problem with Neumann and Dirichlet boundary conditions for the Gellerstedt equation in four variables was investigated. The energy integral method was used to prove the uniqueness of the solution to the problem. In addition to it, formulas for differentiation, autotransformation, and decomposition of hypergeometric functions were applied. The solution was obtained explicitly and expressed by Lauricella’s hypergeometric function.
Төрт өлшемді Геллерстедт теңдеуі үшін шеттік есеп
Краевая задача для четырехменого уравнения Геллерстедта
Keywords: Gellerstedt equation; boundary value problem with mixed conditions; fundamental solution